A Roadmap for Value‐Based Payment Models Among Patients With Cirrhosis. Issue 3 (22nd February 2019) - Volk, Michael L.; Mellinger, Jessica; Bansal, Meena B.; Gellad, Ziad F.; McClellan, Mark; Kanwal, Fasiha
Abstract : Healthcare reimbursement is shifting from fee‐for‐service to fee‐for‐value. Cirrhosis, which costs the U.S. healthcare system as much as heart failure, is a prime target for value‐based care. This article describes models in which physician groups or health systems are paid for improving quality and lowering costs for a given population of patients with cirrhosis. If done correctly, we believe that such frameworks, once adopted, could help reduce burnout by freeing physicians of the burden of checking boxes in the electronic medical record so that they can devote their energies to managing populations. Conclusion : Value‐based payment models for cirrhosis have the potential to benefit patients, physicians, and healthcare insurers.